2010
DOI: 10.1002/asi.21316
|View full text |Cite
|
Sign up to set email alerts
|

Testing an integrative theoretical model of knowledge‐sharing behavior in the context of Wikipedia

Abstract: This study explores how and why people participate in collaborative knowledge-building practices in the context of Wikipedia. Based on a survey of 223 Wikipedians, this study examines the relationship between motivations, internal cognitive beliefs, social-relational factors, and knowledge-sharing intentions. Results from structural equation modeling (SEM) analysis reveal that attitudes, knowledge self-efficacy, and a basic norm of generalized reciprocity have significant and direct relationships with knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
148
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(158 citation statements)
references
References 72 publications
8
148
0
2
Order By: Relevance
“…The direct link between group identification and behavioral intent demonstrated in H4 (in the form of the intent to use the advice gleaned from the information pool) extends the work of Cho et al (2010), who found an indirect link between group membership and intent to contribute information to Wikipedia, through generalized reciprocity. However, because Cho et al (2010) measured intent to contribute information (as opposed to actual contributions) and the present study measured intent to accept advice (as opposed to measuring if such advice was actually followed), future research should examine actual behaviors more closely, in order to see whether people are indeed more likely to heed advice and to change their behavior based on information they receive from those people online with whom they share group identity.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The direct link between group identification and behavioral intent demonstrated in H4 (in the form of the intent to use the advice gleaned from the information pool) extends the work of Cho et al (2010), who found an indirect link between group membership and intent to contribute information to Wikipedia, through generalized reciprocity. However, because Cho et al (2010) measured intent to contribute information (as opposed to actual contributions) and the present study measured intent to accept advice (as opposed to measuring if such advice was actually followed), future research should examine actual behaviors more closely, in order to see whether people are indeed more likely to heed advice and to change their behavior based on information they receive from those people online with whom they share group identity.…”
Section: Discussionsupporting
confidence: 69%
“…However, because Cho et al (2010) measured intent to contribute information (as opposed to actual contributions) and the present study measured intent to accept advice (as opposed to measuring if such advice was actually followed), future research should examine actual behaviors more closely, in order to see whether people are indeed more likely to heed advice and to change their behavior based on information they receive from those people online with whom they share group identity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly, the most likely contributors are males with high Internet skills [18]. As for psychological factors, Wikipedia contributors are largely driven by selfconcept motivation [19], altruistic motivations [20], desires to learn [21], gratification obtained from the engagement [22], and a sense of belonging to the Wikipedia community [23]. In addition, features of articles also play an important role in determining contribution patterns.…”
Section: Related Workmentioning
confidence: 99%